Equal protection : documents decoded - Hudson, David L., 1969- (Documents decoded., 2018)
This book uses primary sources to closely examine the Equal Protection Clause of the Fourteenth Amendment and to show how legal interpretations of it have had a profound impact on American life as we know it. It closely examines the history and development of the Equal Protection Clause and details the many ways in which it has shaped U.S. history, and the impact it has had and may have on American society in the 21st century.